2010
DOI: 10.1097/wnr.0b013e328337ff18
|View full text |Cite
|
Sign up to set email alerts
|

Negative bias of processing ambiguously cued emotional stimuli

Abstract: Daily we cope with upcoming potentially disadvantageous events. Therefore, it makes sense to be prepared for the worst case. Such a 'pessimistic' bias is reflected in brain activation during emotion processing. Healthy individuals underwent functional neuroimaging while viewing emotional stimuli that were earlier cued ambiguously or unambiguously concerning their emotional valence. Presentation of ambiguously announced pleasant pictures compared with unambiguously announced pleasant pictures resulted in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
8
9
0
1
Order By: Relevance
“…Also, a pattern similarity analysis revealed that individuals with a negative valence bias showed amygdala responses to surprised faces that were similar to maintaining negative affect towards negatively valence IAPS scenes during an emotion regulation task. Taken together, this study supports the prevailing hypothesis that positive interpretations of ambiguous stimuli involve mechanisms common to reappraisal during explicit emotion regulation (Neta and Tong, 2016), and is consistent with the notion that negative interpretations tend to be the initial response (Kim et al , 2003; Kaffenberger et al , 2010; Neta and Whalen, 2010; Neta et al , 2011). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, a pattern similarity analysis revealed that individuals with a negative valence bias showed amygdala responses to surprised faces that were similar to maintaining negative affect towards negatively valence IAPS scenes during an emotion regulation task. Taken together, this study supports the prevailing hypothesis that positive interpretations of ambiguous stimuli involve mechanisms common to reappraisal during explicit emotion regulation (Neta and Tong, 2016), and is consistent with the notion that negative interpretations tend to be the initial response (Kim et al , 2003; Kaffenberger et al , 2010; Neta and Whalen, 2010; Neta et al , 2011). …”
Section: Discussionsupporting
confidence: 89%
“…Despite individual differences in ratings of emotional ambiguity, initial responses toward ambiguous stimuli tend to be more negative compared with delayed responses (Kim et al , 2003; Kaffenberger et al , 2010; Neta and Whalen, 2010; Neta et al , 2011; Neta and Tong, 2016). For example, reaction times are longer when rating ambiguous cues as positive compared with negative (Neta and Tong, 2016), and surprised faces are detected more quickly as an oddball among positive (happy) compared to among negative (angry) faces (Neta et al , 2011).…”
Section: Introductionmentioning
confidence: 92%
“…When positive information was presented in an ambiguous manner, brain activity was evident, showing that the subject's brain regarded the positive information as unexpected and was trying to adapt. This suggests that the psychophysiological disposition of an individual is naturally negative, perhaps as a result of having to cope with a large amount of negative events in the normal course of everyday living [38]. To the selector, this means that there is the possibility that one will enter into the selection process with an overly negative or critical bias, expecting to find nothing that is suitable.…”
Section: Studies Of Affective Biasmentioning
confidence: 98%
“…Then the computed value for each channel will compared in order to check which brain hemisphere is more active. Based on previous researches that have been done by [58] [59] [56] [57] and [60], the high computed Mean value positively correlated with the more active hemisphere. After computing the mean value for each T7 & T8 pair channel, the difference between each Mean is computed.…”
Section: Variance Of Brain Hemisphere Activitymentioning
confidence: 99%
“…The orange and yellow colors illustrate the activity region of the brain meanwhile the white blue color illustrates the Inactive region. According to [58] [59] [60] and [61] each induced emotion directly linked of both right and left hemispheres that result emotion. A negative evoked emotion comes when more active on right frontal lobe meanwhile a positive evoked emotion produces when more active left frontal lobe.…”
Section: Variance Of Brain Hemisphere Activitymentioning
confidence: 99%